Implementasi Sistem Pakar Dalam Pemilihan Makanan Tradisional Silungkang - Fadila; Januardi Nasir (LPPM Universitas Ekasakti, 2025)
Traditional food is an essential part of cultural heritage that must be preserved, including the unique culinary offerings of Silungkang, which hold significant historical and sensory value. However, limited access to information and low public awareness have contributed to a declining interest in consuming local traditional food. This study aims to develop an expert system using the forward chaining method to assist users in identifying and selecting Silungkang traditional foods based on specific characteristics and personal preferences. The forward chaining approach was chosen for its ability to infer conclusions from initial facts through the application of IF-THEN rules. The system was designed using PHP as the programming language and MySQL as the database, with a user-friendly web-based interface. The results indicate that the expert system effectively provides accurate and efficient food recommendations, serving both as an educational tool and a medium to promote local culinary heritage. In conclusion, the implementation of this expert system contributes positively to the preservation of traditional food and the reinforcement of Silungkang’s cultural identity through artificial intelligence-based solutions.